2016
DOI: 10.1371/journal.pntd.0004375
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Visceral Leishmaniasis Correlates with Elevated Levels of Serum IL-6, IL-27 and sCD14

Abstract: BackgroundVisceral leishmaniasis (VL) is a severe disease caused by infection with protozoa of the genus Leishmania. Classic VL is characterized by a systemic infection of phagocytic cells and an intense activation of the inflammatory response. It is unclear why 90% of infected individuals do not develop the disease while a minority develop the classical form. Furthermore, among those that develop disease, a small group progresses to more severe form that is unresponsive to treatment. The presence of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
81
4
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 52 publications
15
81
4
13
Order By: Relevance
“…are expert in modulating immune activity through diverse strategies (4). Previous reports on human leishmaniasis indicate that IL-27 increases when the disease is active in both cutaneous (2628) and visceral forms (7, 8). Here, for the first time, plasma levels of IL-27 were evaluated in L. infantum -infected individuals from Europe.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…are expert in modulating immune activity through diverse strategies (4). Previous reports on human leishmaniasis indicate that IL-27 increases when the disease is active in both cutaneous (2628) and visceral forms (7, 8). Here, for the first time, plasma levels of IL-27 were evaluated in L. infantum -infected individuals from Europe.…”
Section: Discussionmentioning
confidence: 95%
“…To address if the increase of systemic IL-27 is a common fact of VL among different endemic areas (7, 8), we determined this cytokine in the plasma of active L. infantum infected individuals from a current outbreak in Spain. Patients with active disease presented higher IL-27 levels than both cured ( p  ≤ 0.001) and negative controls ( p  ≤ 0.001) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of IL-27 has been observed in the serum of patients with VL, which correlated with the severity of the disease (19). Thus, we hypothesized that IL-27 could mediate susceptibility to VL.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the role of IL-27 in the regulation of the immune response can lead to higher parasite replication or to the control of infection. It was recently observed that visceral leishmaniasis patients present high levels of IL-27 in serum, which decreases after successful treatment (19). Thus, we hypothesized that IL-27 plays a role in the regulation of immune response during L. infantum infection, which could exacerbate the disease in a mouse model of visceral leishmaniasis.…”
mentioning
confidence: 95%